صورة الشيطان في العرض المسرحي: مسرحية شيطانكو للكاتب وجيه صبري نموذجا - محمد، ضحى محمد راشد; فرج، فرج عمر علي; مصلحي، شيماء فتحي عبدالصادق; حسين، أمينة عامر بيومي Hussein, Aminah Amer Bayoumi (جامعة الزقازيق - كلية التربية النوعية, 2022)
يعد إتباع الشيطان من أكبر المشاكل التي تحل بالإنسان، لأن خطورة إتباع الشيطان لم تكن في الدنيا فقط بل لها جزاء كبير عند الله في الآخرة، فالشيطان هو مارد من الجن، وتطلق الشيطان على الجن الكافر الذي يدعو إلى السوء والفحشاء، وللشيطان غايات كثيرة وهدفه الأول إدخال الناس في المعصية والبعد عن الله، فيأخذ الشيطان الإنسان من تحت رحمة الله إلى ظلمات الكفر، ولكن يكون نتيجة هذا الإغواء صعب وعسير على الإنسان، فحذر الله تعالي من إتباع الشيطان وأن كل هم الشيطان هو نشر السوء بين الناس وأعلن الله تعالي أن الشيطان هو عدوا للإنسان وإنه يأمر بالسوء والفحشاء. فيسعي الشيطان أيضا إلى وقوع الناس في الكفر وهو أعظم وأكبر ذنب في هذا الكون والشرك بالله والكفر به وهذه من "أكبر غايات الشيطان التي يسعي لها كي يبعد الإنسان عن الله ويوسوس كي يفعل المعاصي التي تغضب الله، وإبعاد أعدائه عن الجنة، ويسعي الشيطان أيضا للصد عن سبيل الله وإعلان الحرب عن دينه والصراط المستقيم، ويدخلهم في الضلال عن الحق والاتجاه إلى الكيد لأهله، فحذر الله تعالي من إتباع الشيطان وأعلن الله عن عواقب لمن يتخذ الشيطان في طريقه. فعواقب إتباع الشيطان لم تقتصر على الدنيا فقط، فمن يتبع الشيطان سوف ينال جزاءه في الدنيا والآخرة، فقد خص الله تعالي إبليس أبا الشياطين بعقوبة تختلف عن باقي الشياطين، فقد ضرب الله عليه اللعنة منذ أن رفض السجود لأبينا آدم عليه السلام، فتوعد الله إلى من يتبع الشيطان في الدنيا بعاقب كبيرة، وإنه سوف ينزل عليه الشقاء والبلاء وخسارة الدنيا. يتضح أن الله توعد لمن يسلك نهج الشيطان وليس له راحة في الدنيا وله معيشة ضنك ويشعر دائما بعدم ارتياح وتوفيق أن حياته ستسود فيها الظلام والقلق والخيرة، وهذا هو الشقاء الذي قال الله عنه لمن يتبع ويسلك طريق الشيطان، فالشيطان لا يترك من يتبعه في راحة فإنه يجلب له القلق والحياة والشك وعدم الاستقرار وتشتت الأفكار فهو لا يترك عقل الإنسان في راحة، ولم تنتهي عواقب الشيطان في الدنيا فقط بل تمتد إلى الأخرة أيضا، وهو العذاب الأكبر الذي تصوره آيات الكتاب العزيز بأنه سوف يحشر إبليس وأتباعه في المحشر ويخلد في النار هو وأتباعه، ومع كل مكر الشيطان ودفع الإنسان للخطأ سوف يتبرأ منهم الشيطان أمام الله وهذا أكبر حسرة وندامة يقع فيها أتباع الشياطين وأعلن الله عن ذلك كتابه العزيز وهذه هي القوة الناعمة التي مدنا بها الله في القرآن الكريم وهي معرفة ما ينوي إليه الشيطان. فالإستعاذة بالله من الشيطان الرجيم تبعد الشيطان عنا وتحمينا من كل سوء ومكروه يدعو له الشيطان، ويجب الاستعانة دائما بالمعوذتين وكلماتها المحصنة من قرب الشيطان وإبعاده عنا وعي أفضل وسيلة لحفظ الإنسان وأن لا يقربنا الشيطان. فتبين هذه الدراسة طرق الشيطان لإغواء الإنسان ووقوعه في المعاصي وكيفية التخلص من مكر وكيد الشيطان وإبعاده عن الإنسان. Following the devil is one of the biggest problems that a human being can fall in, because the danger of following the devil was not only in this world, it also has a great pay from god in the afterlife, as the devil is a genie of the jinn and the name devil is given to the jinn who calls to evil and immorality, also the devil has many goals and the main goal is leading people into disobedience and being far from god, so he takes people from the mercy of God into the darkness of unbelief, but the result of this is very severe for a person as God Almighty warned against following the devil and the all the devil’s concern is to spread evil among people, as God Almighty declared that the devil is the enemy of a human being and that he commands evil and immorality. As the devil seeks to cause people to fall into disbelief, which is the greatest sin in the universe, although he whispers to man to do the sins that makes God angry in order to keep him away from paradise, as he seeks to block the path of God and declare war and lead people into misguidance from the truth. The consequences of following the devil aren’t confined to this world only; whoever follows the devil will receive his severe in this world and in the afterlife. God Almighty has singled out the devil, the father of devils with a punishment that is different from the rest of the devils. God has cursed him since he refused to prostrate to our father Adam, peace be upon him, so God has promised that who will follow the devil in this world will get a great punishment and will descend upon his misery, affliction and loss of this world. It’s clear that God has promised to those who will follow the path of the devil that they will have no rest in this life and will have a hard life and will always feel uncomfortable and unsuccessful, as his life will prevail in darkness, anxiety, and this is the misery that God said about who will follow and take the path of the devil, as the devil doesn’t leave who follow him to live in peace, he brings him anxiety, life doubt, instability and dispersal of thoughts. He doesn’t leave the human mind at rest, and the consequences of following the devil don’t end in this world only, but extend to the life after as well and it’s the greatest torment that the verses of the dear book envision that he will resurrect the devil. As his followers will be gathering in hell. Seeking refuge with Allah from the accursed devil keeps the devil away from us and protects us from every evil that the devil calls people for, as we must always seek help from the two refuges and their fortified words to keep the devil away from us. This study shows the ways of the devil to convince man to fall into sin, and how to get rid of the deception, plot of the devil and keep him away from the human being.
Keywords: الفن المسرحي -- صبري، وجيه -- شخصية الشيطان -- العروض المسرحية